Epidemiological relevance of dogs for the prevention of Toxoplasma gondii, Neospora caninum and Leptospira spp. - Fernanda Pinto-Ferreira; Aline Kuhn Sbruzzi Pasquali; Vanete Thomaz-Soccol; Regina Mitsuka-Breganó; Eloiza Teles Caldart; André de Souza Leandro; Luciana Chiyo; Eliane Maria Pozzolo; Patrícia Cubas; Lucienne Garcia Pretto Giordano; Ricardo Rasmussen Petterle; Italmar Teodorico Navarro (Revista Brasileira de Parasitologia Veterinária)
Abstract This study evaluated the seroprevalence of Toxoplasma gondii, Neospora caninum and Leptospira spp. in dogs from Foz do Iguaçu, Paraná, Brazil. Indirect immunofluorescent antibody test was used to detect antibodies anti-T.gondii and anti-N. caninum. Immunoenzymatic assay and microscopic serum agglutination were used for screening antibodies anti-T.gondii and anti-Leptospira spp., respectively. The results were: 67.02% of the samples reactive for T.gondii and 1.38% for N. caninum, both without statistically significant variables. For Leptospira spp. the results indicated seroprevalence of 23.11%. The analysis of the variables without distinction of serovar showed association for intrinsic characteristics as breed, age, nutritional status and dog category. The extrinsic variables as city region and access to the street presented association (p<0.05). The most prevalent serovars were: Canicola 59.47%; Bratislava 13.07% and Butembo 15.68%. Variables that make up the adjusted multiple analysis model using Leptospira spp. were: age, breed and nutritional status; serovar Canicola, sex, nutritional status and area (p<0.05); serovar Bratislava, lymphadenomegaly and presence of fleas (p<0.05). Given the results obtained, dogs can be used as sentinels for toxoplasmosis and leptospirosis in Foz do Iguaçu and other cities with similar outcomes. In addition, preventive measures should be taken by health authorities because they are zoonoses and humans are also at risk.